Evaluasi Program Bimbingan Teknis Penyusutan Arsip Dinamis di Dinas Kelautan Dan Perikanan Provinsi Jawa Timur - Latifatun Nur Azizah; Weni Rosdiana; Nabila Septia Rosa (Policy and Maritime Review, 2026)
Dynamic records disposition is an important activity in records management to ensure efficiency, reduce records accumulation, and support administrative order. The East Java Provincial Marine and Fisheries Service conducted a Technical Guidance Program on Dynamic Records Disposition to improve the competencies of records managers in divisions, Technical Implementation Units (UPTs), and branch offices. This study aimed to evaluate the implementation of the program using the CIPP (Context, Input, Process, Product) evaluation model. This study employed a qualitative descriptive method. Data were collected through observation, interviews, and document analysis. The informants consisted of archivists and program participants. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the program was relevant to organizational needs, as differences in understanding and skills among records managers in implementing records disposition still existed. The program was supported by regulations, competent instructors, and relevant materials, although limitations in facilities and human resource readiness remained. The implementation was carried out according to plan through lectures, discussions, and practical sessions, but faced challenges related to limited time and varying participant competencies. The program improved participants’ understanding of dynamic records disposition procedures; however, its implementation in work units was not yet optimal. Overall, the program was considered fairly effective but requires stronger follow-up, monitoring, and mentoring to support sustainable implementation.